2020
DOI: 10.1038/s41419-020-2323-5
|View full text |Cite
|
Sign up to set email alerts
|

Silencing lncRNA Lfar1 alleviates the classical activation and pyoptosis of macrophage in hepatic fibrosis

Abstract: Hepatic fibrosis is a common pathological consequence of a sustained wound healing response to continuous liver injury, characterized by increased production and accumulation of extracellular matrix. If unresolved, the fibrotic process results in organ failure, and eventually death after the development of cirrhosis. It has been suggested that macrophages play central role in the progression of hepatic fibrosis, which is related to inflammation and pyroptosis, a novel programmed and proinflammatory cell death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Therefore, researchers began to focus on the role of inflammation and immune response caused by cholestasis on liver injury [24,25]. The literature reported that 24 h after bile duct ligation, a large number of inflammatory cells infiltrated around the injured liver tissue [26,27]. Our study also showed the necrosis of diseased hepatocytes accompanied by inflammatory cell infiltration in mice 48 h after ANIT administration.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, researchers began to focus on the role of inflammation and immune response caused by cholestasis on liver injury [24,25]. The literature reported that 24 h after bile duct ligation, a large number of inflammatory cells infiltrated around the injured liver tissue [26,27]. Our study also showed the necrosis of diseased hepatocytes accompanied by inflammatory cell infiltration in mice 48 h after ANIT administration.…”
Section: Discussionmentioning
confidence: 52%
“…Pyroptosis has been implicated in various diseases, such as inflammation, nonalcoholic fatty liver disease, and liver fibrosis 28 31 . Bacteria, toxins and so on can elicit a strong immune response in macrophages, resulting in pyroptosis 29 , 32 . However, the molecular basis of Kupffer cells pyroptosis is incompletely understood, which has limited the identification of therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“… 16 LPS are involved in activating caspase-11 in mice and caspase-4 and -5 in humans, 17 19 and LPS and ATP have been shown to markedly upregulate the expression levels of pyroptosis-related genes that activate the NLRP3 inflammasome. 20 Additionally, LPS induces caspase-11 in mice to activate the GSDMD protein and trigger non-canonical pyroptosis, while caspase-4 and -5 in humans have similar functions and stimulate the innate cellular immune response. 21 23 In mice with sepsis, the continuity of the neural nuclear and mitochondrial membrane suffers from injury, suggesting that neurons undergo pyroptosis.…”
Section: Discussionmentioning
confidence: 99%